Mitophagy in ischemic heart disease: molecular mechanisms and clinical management - Shujuan Xu; Zihan Wang; Fan Guo; Yehao Zhang; Han Peng; Huiyu Zhang; Zixin Liu; Ce Cao; Gaojie Xin; Yuan Yuan Chen; Jianhua Fu (Cell Death and Disease)
Abstract The influence of the mitochondrial control system on ischemic heart disease has become a major focus of current research. Mitophagy, as a very crucial part of the mitochondrial control system, plays a special role in ischemic heart disease, unlike mitochondrial dynamics. The published reviews have not explored in detail the unique function of mitophagy in ischemic heart disease, therefore, the aim of this paper is to summarize how mitophagy regulates the progression of ischemic heart disease. We conclude that mitophagy affects ischemic heart disease by promoting cardiomyocyte hypertrophy and fibrosis, the progression of oxidative stress, the development of inflammation, and cardiomyocyte death, and that the specific mechanisms of mitophagy are worthy of further investigation.